2005
DOI: 10.1111/j.1600-0404.2005.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in headache patients? A clinical study

Abstract: Hypertension could be one of the factors leading to exacerbation of the frequency and severity of attacks, both in migraine and tension-type headache. Hypertension has important therapeutic implications and should be actively sought in headache patients, and more thoroughly investigated, with ad-hoc surveys in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
(37 reference statements)
3
19
1
Order By: Relevance
“…But hypertension could also be one of the factors leading to exacerbation of the frequency and severity of attacks, both in migraine and tension-type headache, and the evidence supporting a connection between chronic hypertension and headache is scant [15, 19]. As a result, in our study hypertension was not found to be a major factor in the differentiation of secondary headaches from primary ones.…”
Section: Discussioncontrasting
confidence: 57%
“…But hypertension could also be one of the factors leading to exacerbation of the frequency and severity of attacks, both in migraine and tension-type headache, and the evidence supporting a connection between chronic hypertension and headache is scant [15, 19]. As a result, in our study hypertension was not found to be a major factor in the differentiation of secondary headaches from primary ones.…”
Section: Discussioncontrasting
confidence: 57%
“…Prevalence of alcohol use was 74.5% and cigarette smoking 75% in those with CH.Only males included in this study.Liang, 2013 [18]673 male and female CH patients from a Taiwanese National Health DatabaseRetrospective cohort study with 2.5 year median follow-up duration3.6% developed depression over study period. Adjusted HR 5.6% vs. controls but not different from those with migraine; number of bouts/year of CH a risk factor for depression.Study limited to patients diagnosed by neurologist and prescribed standard CH drugs; excluding those with previous psychiatric diagnoses (104 of original 777; 13%).Pietrini, 2005 [19]60 consecutive male and female CH patients seen at an Italian headache centerCross-sectional, based on study examination35% had hypertension, defined as blood pressure ≥ 140/90 on average of 3 blood pressure readings.The authors concluded that the prevalence of hypertension in this group was within expected range given age and sex.Robbins, 2012 [20]49 consecutive male and female CH patients seen in a New York headache clinic over a 3.5 year periodCross-sectional chart reviewPrevalence of depression (PHQ ≥ 1 0) was 6.3% in episodic CH, 11.8% in chronic CH; Anxiety (GAD-7 ≥ 10) prevalence was 15.6% in episodic CH and 11.8% in chronic CH. Prevalence of hypertension was 14%, current or former cigarette smoking was 65.3% and GERD was 8%.Rossi, 2012 [21]210 consecutive male and female CH patients from two Italian headache centersCross-sectional interview and anonymous survey data92.5% of male CH patients and 85.4% of female CH patients reported current or past use of tobacco, statistically significantly higher than prevalence in general population.Self reported data on substance use.Rozen, 2012 [22]1134 US male and female CH patients responding to an internet surveyCross-sectional survey (internet)Prevalence of depression was 24%, suicidal ideation was reported by 55%, sleep apnea by14%, restless leg syndrome by 11%, asthma by 9%.…”
Section: Introductionmentioning
confidence: 99%
“…According to the current knowledge, arterial hypertension is believed to enhance the effects of migraine on the vascular wall and concur to the further impairment of the endothelial function in the cerebral vasculature, leading to exacerbation of the frequency and severity of attacks [1,3,4]. In addition, individuals with migraine and hypertension have a higher risk of developing cardiovascular disease, such as ischemic stroke, than normotensive individuals [2,5].…”
Section: Introductionmentioning
confidence: 99%